End of 9-endings and price perceptions - Haipeng Chen; Daniel C. Levy; Avichai Snir (Bar-Ilan University, Department of Economics, 2017)
We take advantage of a natural experiment to document an emergence of a new price ending that has the same effects as 9-endings. In January 2014, the Israeli parliament has passed a law prohibiting the use of non 0-ending prices. We find that one year after 9-ending prices have disappeared, 90-ending prices acquired the same status as 9-ending prices had before the law was passed. 90-ending prices became the new psychological price points. The retailers and the shoppers both reacted to the regulatory intervention optimally, which has eliminated the regulation's intended effect.
Keywords: E31; L16; K20; 330; 9-ending prices; psychological price points; sticky prices; rigid prices; price recall; price control; price regulation; integer constraint